The Role of the Teacher as a Facilitator in the Islamic Religious Education Learning Process - Mawaddah, Nurul (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This paper discusses the role of teachers as facilitators in the learning process of Islamic religious education in state elementary schools. The main problem is what the reality is in the Islamic religious education learning process at Public Elementary School 91 Pammana. What are the factors that hinder the teacher's role as a facilitator in the Islamic Religious Education learning process, and what is the teacher's role as a facilitator in the Islamic Religious Education learning process? The author uses a qualitative descriptive research method in the form of written words from previously determined people. Meanwhile, for data collection, namely field research, the authors conducted interviews with school principals, Islamic religious education teachers, and students. The reality discovered by researchers in the field, namely the reality that occurred in the Islamic Religious Education learning process at Public Elementary School 91 Pammana in Wajo Regency in the pre-Covid-19 period when face-to-face learning was still implemented for lower grades, such as grades II and III, teachers Sometimes it still dominates learning, or it could be said that learning is still teacher-centered. For high classes, such as classes IV and V, the teacher has acted as a facilitator. During the COVID-19 pandemic, learning is done online or from home. Factors inhibiting the role of teachers as facilitators in the Islamic Religious Education learning process at Public Elementary School 91 Pammana in Wajo Regency: there are two inhibiting factors, including internal factors, in the form of the teacher's old habits in teaching. Meanwhile, external factors include the lack of supporting facilities owned by the school. The teacher's role as a facilitator in the learning process has been implemented, but it is not perfect.